Heterogeneous nanozymatic activity of Hf oxo-clusters embedded in a metal–organic framework towards peptide bond hydrolysis. Issue 28 (13th July 2021) - Moons, Jens; Loosen, Alexandra; Simms, Charlotte; de Azambuja, Francisco; Parac-Vogt, Tatjana N.
Abstract : A Hf-based NU-1000 metal organic framework as a hydrolytic nanozyme for peptide bonds in dipeptides and hen egg white lysozyme protein showed greater stability and better recyclability than previous Zr-/Hf-based nanozymes. Abstract : Materials with enzyme-like activities and proteolytic potential are emerging as a robust and effective alternative to natural enzymes. Herein, a Hf6 O8 -based NU-1000 metal organic framework (Hf-MOF) is shown to act as a heterogeneous catalyst for the hydrolysis of peptide bonds under mild conditions. In the presence of Hf-MOF, a glycylglycine model dipeptide was hydrolysed with a rate constant of k obs = 8.33 × 10 −7 s −1 (half-life ( t 1/2 ) of 231 h) at 60 °C and pD 7.4, which is significantly faster than the uncatalyzed reaction. Other Gly-X peptides (X = Ser, Asp, Ile, Ala, and His) were also smoothly hydrolysed under the same conditions with similar rates, except for the faster reactions observed for Gly-His and Gly-Ser. Moreover, the Hf6 O8 -based NU-1000 MOF also exhibits a high selectivity in the cleavage of a protein substrate, hen egg white lysozyme (HEWL). Our results suggest that embedding Hf6 O8 oxo-clusters is an efficient strategy to conserve the hydrolytic activity while smoothing the strong substrate adsorption previously observed for a discrete Hf oxo-cluster that hindered further development of its proteolytic potential. Furthermore, comparison with isostructural Zr-NU-1000 shows that although the Hf variant afforded the same cleavage pattern towards HEWL but slightly slower reaction rates, it exhibited a larger stability window and a better recyclability profile. The results suggest that these differences originate from the intrinsic differences between Hf IV and Zr IV centers, and from the lower surface area of Hf-NU-1000 in comparison to Zr-NU-1000.